2008
DOI: 10.1111/j.1582-4934.2008.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminal 37 residues of LRP promote the amyloidogenic processing of APP independent of FE65

Abstract: The major defining pathological hallmark of Alzheimer's disease (AD) is the accumulation of amyloid β protein (Aβ), a small peptide derived from β- and γ-secretase cleavages of the amyloid precursor protein (APP). Recent studies have shown that the Low-density lipoprotein receptor-related protein (LRP) plays a pivotal role in the trafficking of APP and generation of Aβ. In particular, we recently showed that the soluble cytoplasmic tail of LRP (LRP-ST) without a membrane tether was sufficient to promote Aβ gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…In transiently transfected HEK293T cells, RanBP9 markedly enhanced the levels of A␤ in the conditioned medium (supplemental Fig. S1), similar to that seen with the soluble LRP-C37 polypeptide (7). To confirm these results in a different cellular system, we stably transfected FLAG-RanBP9 in CHO cells stably expressing APP751 (CHO-APP751).…”
Section: Endogenous Ranbp9 Interacts With Lrp and App In Brain-mentioning
confidence: 74%
See 1 more Smart Citation
“…In transiently transfected HEK293T cells, RanBP9 markedly enhanced the levels of A␤ in the conditioned medium (supplemental Fig. S1), similar to that seen with the soluble LRP-C37 polypeptide (7). To confirm these results in a different cellular system, we stably transfected FLAG-RanBP9 in CHO cells stably expressing APP751 (CHO-APP751).…”
Section: Endogenous Ranbp9 Interacts With Lrp and App In Brain-mentioning
confidence: 74%
“…Although we had hypothesized that one or more NPXY domains in LRP-ST might underlie the pro-amyloidogenic processing of APP, we recently found that the 37 C-terminal residues of LRP (LRP-C37) lacking the NPXY motif was sufficient to robustly promote A␤ production independent of FE65 (7). Because LRP-C37 likely acts by recruiting other proteins, we used the LRP-C37 region as bait in a yeast two-hybrid screen, resulting in the identification of 4 new LRP-binding proteins (7). Among these, we focused on Ran-binding protein 9 (RanBP9) in this study, which we found to play a critical role in the trafficking and processing of APP.…”
mentioning
confidence: 99%
“…The yeast two-hybrid screening was performed in the AH109 yeast strain, which contains three reporters (ADE2, HIS2, and MEL1). The bait plasmid was initially transformed into AH109, and growth was selected in SD dropout plates lacking tryptophan as described previously (15). These yeast strains expressing the RanBP9-LisH or RanBP9-SPRY domains were then used individually for mating with the Tyr-187 mating strain transformed with a cDNA library made from human brain and plated them on SD dropout plates lacking adenine, histidine, leucine, and tryptophan.…”
Section: Methodsmentioning
confidence: 99%
“…Lakshmana and coworkers showed that LRP1 can promote amyloidogenic processing of APP also independent of Fe65, as only the last 37 C-terminal residues of LRP1 cytoplasmic tail, which do not contain the NPxY domains, possess this potential [110]. Furthermore, they identified four new proteins that can bind LRP1 irrespective of the NPxY domains [110].…”
Section: Peripheral Ab Clearance By Lrp1mentioning
confidence: 94%